Family functioning and self-concept in adolescents of a school in Guaranda (Ecuador) - Del Salto-Martínez, Marcelo Zamir (2024)
The objective of this research was to analyze the relationship between family functioning and self-concept in adolescents of an educational unit in Guaranda city, Ecuador. Based on previous research and preliminary observations in the institution, it has been considered that dysfunctionality in the family nucleus, limits the true potential of adolescents. The methodology was based on the post-positivist paradigm, it is quantitative, it is descriptive and correlational, non-experimental and cross-sectional. The Family Functioning Perception Questionnaire and the Self-Concept Form 5 were used, 372 students between 15 and 19 years old, from the second and third grades of high school participated, 56.2% female and 43.8% male. Moderate scores were obtained in both family functioning and self-concept. A moderate positive correlation was obtained (r=0.422; p: 0.01), leading to the conclusion that the higher the family functioning, the higher the self-concept in adolescents.